If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9w + 8w + 2 = -3 Reorder the terms: 2 + -9w + 8w = -3 Combine like terms: -9w + 8w = -1w 2 + -1w = -3 Solving 2 + -1w = -3 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1w = -3 + -2 Combine like terms: 2 + -2 = 0 0 + -1w = -3 + -2 -1w = -3 + -2 Combine like terms: -3 + -2 = -5 -1w = -5 Divide each side by '-1'. w = 5 Simplifying w = 5
| 26m=650 | | 6(v-5)(5v+8)=0 | | 4(2L+1)=111 | | -11-n=-11 | | 3x+(x+38)=90 | | 14=5+h | | U-1=-4 | | -46=p-19 | | 8a-4-3a=12 | | 13-4x=-x-31 | | (x+54)+2x=90 | | 8x-4=-1 | | (x+54)+2x=180 | | 6(3x+5)=100 | | 6x+7c=37cforx | | 12x^2+105x+147=35 | | .2t+1.8=1.2 | | -.2t+1.8=1.2 | | 5x+(x-24)=180 | | .97n+5.95=11.57 | | 4(-8+5)=-32(0.44)-26 | | 0=7(6x-11)+2x+6 | | 5w-5=8w+16 | | 4(-8+5)=-32(3)-26 | | 16y^2+7y+10= | | x^3-x^2-x=-2x | | 1a^2-2a-7=0 | | 9x+-34=-88 | | 7x+28-4x-4=5 | | x=2mx-8b | | -5(5x-3)-27=-3(3x-2) | | 7b-4(3b+7)=7-(8+8b) |